Functionalized MXene Enabled Sustainable Water Harvesting and Desalination. (10th July 2020) - Fei, Jipeng; Koh, See Wee; Tu, Wenguang; Ge, Junyu; Rezaeyan, Hamid; Hou, Shuai; Duan, Hongwei; Lam, Yee Cheong; Li, Hong
Abstract: Solar irradiation is a promising resource for sustainable energy conversion and storage in many technological fields. Interfacial solar steam generator is emerging as a sustainable system for water harvesting under natural solar irradiance. However, natural sunlight is usually insufficient for conventional interfacial (2D absorber) solar steam generators to achieve high solar steam efficiency (>85%). Herein, a functionalized MXene‐polymeric membrane‐based solar steam generator in a heat localization structure is reported as an efficient water harvesting and desalination system. The functionalized MXene flakes are homogeneously dispersed and encapsulated in polymeric networks of cellulose acetate in the crosslinking process, where water is automatically pumped through the absorber in the embedded nano/micro channels. As such, the fabricated solar steam generator shows a net evaporation rate (with respect to that in the dark condition) of 1.47 kg m −2 h −1 with 92.1% efficiency under 1 sun illumination. Moreover, the salt rejection rate for high salinity seawater (original Na + concentration is 18 000 mg L −1 ) reaches up to 97.5%, generating drinkable water that meets the WHO standard. The new photothermal membrane absorber is cost‐effective, scalable, washable, and stable under harsh conditions; holding great promise for practical solar desalination applications. Abstract : Li‐intercalated MXene flakes can greatly enhance light absorption owing to the expanded interlayer gap during intercalation. The cellulose acetate polymeric network that completely wraps around MXene flakes efficiently prevents heat loss and provides sustainable water transport through capillary force. Efficient steam generation is believed to arise from the increased light absorption and excellent heat isolation.